Evaluation of the working mechanisms and simplified models of endplate-type inter-module connections. (August 2021) - Zhao, Fengtao; Yu, Yujie; Lin, Siwen; Ding, Faxing
Abstract: In modular steel buildings, factory prefabricated volumetric modules are assembled onsite to form permanent buildings. The inter-module connections provide a path for load transfer between modules. In this study, the detailed working mechanisms of different load-transfer components in endplate-type inter-module connections are investigated systematically. The effectiveness of commonly used simplified models for inter-module connections is evaluated, and a simplified analytical model with multiple springs is proposed on the basis of cooperative working interactions. The results indicate that the tensile strength of inter-module connections is dramatically lower than the compressive strength, and the moment transfer abilities are closely correlated with the tensile strengths. The horizontal shear resistance is provided initially through contact friction between connected columns, and the shear strength calculations need to consider the contribution of axial loads in module columns. Vertical dislocations between horizontally arranged modules are resisted through inclusion of a continuous gusset plate. The vertical shear resistance of interior inter-module connections can then be calculated based on the shearing action of the intermediate gusset plate within the gap region between horizontally connected columns. The out-of-plane prying deformation at endplates and different stiffnesses and strengths at different load-transfer components lead to nonuniform rotations between connected columns in the connections. The proposed model can effectively simulate the detailed load-transfer abilities of inter-module connections and can be easily applied to the structural analysis of modular steel buildings.